Digital applications for developing creative writing competence in primary education - Silvia GOLUBITCHI; Georgeta CRIVOI (Acta et Commentationes, Sciences of Education, 2026)
The development of creative writing competence in primary education is a current educational priority, contributing to the coherent and original expression of ideas and to the development of critical thinking, metacognitive reflection, and self-regulated learning. Writing becomes a complex process of meaning construction based on analysis, synthesis, and evaluation. The integration of ICT transforms writing into a multimodal and interactive activity, facilitating planning, drafting, and collaboration. Thus, students simultaneously develop linguistic and digital competences necessary for effective, creative communication and adaptation in a dynamic educational and socio-professional environment.